Peningkatan Inovasi Kewirausahaan Melalui Praktek Pengolahan Buah Naga Menjadi Stik Mahasiswa Semester IV Kelas B - Leni Saleh; Endang Sumiratin; Defi Juliani; Sebriani Sebriani (Jurnal Pelayanan Masyarakat, 2025)
One form of activity to foster students' interest in developing an entrepreneurial spirit is by providing direct practice on dragon fruit stick processing skills. This training activity was held in Class A1 of the Faculty of Agriculture, Lakidende University, Unaaha. The activity began with a lecture method, after that, the session continued with the core activity, namely the implementation of dragon fruit stick making practice. The training activity on processing dragon fruit into sticks for 4th semester Agribusiness students, class B, who are taking the Entrepreneurship course at the Faculty of Agriculture, Lakidende University, has gone well. This activity also received a positive response from the students who became participants and were able to make good contributions. 83.33% of 4th semester class B students who participated in the training were able to make dragon fruit sticks and 16.67% of participants were not able to make dragon fruit sticks. This training is expected to be a means for students to improve their entrepreneurial spirit and be interested in making new innovations from other agricultural commodities.